PENGARUH KEGIATAN EKSTRAKURIKULER TARI TERHADAP PERKEMBANGAN KECERDASAN KINESTETIK SISWA DI MI AN NUR ASTANA JENU TUBAN - Agus Fathoni Prasetyo; Dewi Tsalis Nur Habibati (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2020)
This study aims to explain the effect of dance extracurricular activities on the development of students' kinesthetic intelligence. The theories used as a foundation in the implementation of this research include the theory of kinesthetic intelligence, extracurricular notions and the theory of dance learning. This research is expected to provide answers to the formulation of the problem: (1) how is the process of extracurricular dance activities at MI An Nur Astana Jenu Tuban? (2) How is the kinesthetic intelligence of the students at MI An Nur Astana Jenu Tuban? (3) is there any influence of extracurricular dance activities on the development of kinesthetic intelligence of students at MI An Nur Astana Jenu Tuban? Referring to the formulation of the problem, the research objectives to be achieved are as follows: (1) To determine the extracurricular activities of dance at MI An Nur Astana Jenu Tuban. (2) To determine the kinesthetic intelligence of students at MI An Nur Astana Jenu Tuban. (3) To determine whether or not there is an effect of extracurricular dance activities on the kinesthetic intelligence of students at MI An Nur Astana Jenu Tuban. This study used a survey method with a quantitative approach through descriptive correlational analysis techniques and regression using parametic statistics. From the research results, it can be concluded that the extracurricular activities of dance have an influence on students' kinesthetic intelligence. The result of the calculation of the product moment correlation variable X and variable Y reached a value of 0.554. This result is greater than the r table, which is 0.468, so that the hypothesis can be concluded by the researcher